Polimorfismo conformacional no modafinil investigado através de cálculos DFT e espectroscopia vibracional - Paschoal, Alexandre Rocha (2007)
Polymorphism, de ned as the ability of a molecule (or a set of molecules) to adopt several packing arrangements, became, in the last decades, a eld of research on its own. Among other advantages of studying polymorphic systems, one can cite the study of the in- uence of molecular packing on solid-state properties, a better understanding of nucleation and crystal growth mechanisms. These advantages became relevant due to their impacts on the control of bioavailability and processes in pharmaceutical industry. In the present work we study the polymorphism of a pharmaceutical substance, the moda nil, which is the active pharmaceutical ingredient (API) of the Provigil R. Moda nil, whose chemical name and structural formula are, respectively, 2-[(diphenylmethyl)sul nyl]acetamide and C15H15NO2S, is indicated in the treatment of narcolepsy, speci cally the excessive daytime sleepiness (EDS), which is a narcolepsy side e ect. Up to now, seven polymorphic forms of moda nil have been observed and the polymorphic forms I and III are the most stable ones. The determination of the crystalline structures of the forms I and III showed that there are two independent molecules, which are enantiomers, in each one of these polymorphs. Besides, moda nil has been crystallized in the forms R and S obtained after the separation of the enantiomers. DFT calculations were performed to investigate the conformational stability of the molecules of moda nil. The main torsions of the molecules were scanned in order to identify the stable conformations, which were compared with independent ones obtained from the crystalline structures determined experimentally. For each calculated conformation, we also calculated the vibrational spectra. These theoretical results were compared with the Raman spectra of the polymorph III of moda nil. In such a way, the main features of the vibrational spectra that allow the polymorph discrimination were correlated with molecular groups associated to these vibrational modes providing an insight into the intra- and intermolecular interaction associated to the polymorphism of moda nil.